A case of unilateral neutrophilic dermatosis of the dorsal hands - Ana G. Lopes; Maria J. Guimarães; Catarina Cerqueira; Cristiana Macedo; Joana Gomes; Celeste Brito (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Our case focuses on a 60-year-old male patient, a farmer, with a previous diagnosis of myelodysplastic syndrome, under regular surveillance at the haemato-oncology department. The patient was referred to the emergency room with an inflammatory ulcerated plaque in the dorsum of his left hand, with 2 weeks evolution. There were two moderately swollen, very painful ulcerated plaques on the dorsal aspect of the left hand, with grayish borders and irregular margins. A skin biopsy showed panniculitis and a dense neutrophilic dermal infiltrate. Attending to his underlying disease, clinical hallmarks of the lesion, and skin biopsy, the diagnosis of a neutrophilic dermatosis of the dorsal hands was made. The patient was treated with oral prednisolone 0.5 mg/kg/day and colchicine 1mg/day with complete regression after 1 month. Neutrophilic dermatosis is a heterogeneous group of skin diseases characterized by dense infiltration of neutrophils in the affected tissue. Neutrophilic dermatosis of dorsal hands is one of them and is considered a localized variant of Sweet Syndrome. The etiology is unknown, but about half of the cases are associated with hematological diseases.